Pengaruh Kelas Kemiringan Lereng dan Penggunaan Lahan terhadap Sifat Fisik Tanah di Kawasan Penyangga Waduk Cirata Kecamatan Cipeundeuy Kabupaten Bandung Barat - Apong Sandrawati; Ade Setiawan; Gilang Kesumah (Fakultas Pertanian Universitas Padjadjaran, 2016)
Waduk Cirata is one of impormant water reservoir in West Java. This reservoir was used for supporting power plants for Java and Bali’s area. It’s need more attention to keep the function continuity of Waduk Cirata. Greenbelt area was one of factor determinant for establishment of Waduk Cirata. Landuse change in greenbelt area is a great threat for greenbelt area sustainability, future more to establishment of Waduk Cirata. This research was aimed to study the effect of landuse and slope combination to physical property of soil. The research was conducted in greenbelt area of Waduk Cirata, located in Margalaksana and Nenggeleng Village, Cipeundeuy District, Bandung Barat. The independent variable was three landuse type and two class of slope, so that were six combination variable that repeated four times, so there was 24 land unit. This land unit determinedwith overlay tools in ArcGIs software. Statistical analysis used for determined the effect andrelationship between parameter. Based on analysis data, combination of landuse type and class of slope not influence bulk density, porosity, and permeability value. Rubber plantation with class of slope 8-15% has higher bulk density (1.24 g/cm3) and higher porosity (66.7 %), meanwhile, the higher of permeability (9.31cm/hour) found in cocoa plantation with class of slope 16-25%.Keywords: greenbelt area, landuse, class of slope, bulk density, porosity, permeability.